2009
DOI: 10.1007/bf03218690
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of thermosensitive nanoparticles based on PNIPAAm core and chitosan shell structure

Abstract: Noble thermosensitive nanoparticles, based on a PNIPAAm-co-AA core and a chitosan shell structure, were designed and synthesized for the controlled release of the loaded drug. PNIPAAm nanoparticles containing a carboxylic group on their surface were synthesized using emulsion polymerization. The carboxylic groups were conjugated with the amino group of a low molecular weight, water soluble chitosan. The particle size of the synthesized nanoparticles was decreased from 380 to 25 nm as the temperature of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…27,28 The influence of organomodified clay towards the various properties of different polymers has been studied but least on rubber-clay composites. 10,29,30 The improvement greatly depends on the distribution of the layers of the silicates in the polymer matrix. If the layers are well ordered and the polymer chains are inserted into the gallery space of the silicate there is an intercalated structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The influence of organomodified clay towards the various properties of different polymers has been studied but least on rubber-clay composites. 10,29,30 The improvement greatly depends on the distribution of the layers of the silicates in the polymer matrix. If the layers are well ordered and the polymer chains are inserted into the gallery space of the silicate there is an intercalated structure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] This is mainly attributed to the nanoscale dimension of silicate layers dispersed in the polymer matrix, which causes a strong interfacial interaction between silicate layers and polymer chains leading to a drastic effect on thermal stability, mechanical, physical, barrier and optical properties with impressive fire resistance properties as compared to pristine polymers. [12][13][14][15][16][17][18] Clay minerals have been extensively used as a reinforcing agent because of their low cost and easy availability 14,19,20 compared to other layered materials.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, semitelechelic PNIPAAm was grafted on chitosan film having amino groups (surface graft) or dissolved together with chitosan in acetic acid to form bulk graft [24]. Similar approach for synthesis of thermosensitive nanoparticles based on PNIPAAm core and chitosan shell was applied by Jung et al [25]. PNIPAAm core nanoparticles containing carboxylic groups on their surface were synthesized by emulsion copolymerization between NIPAAm and acrylic acid (AAc) as a copolymer (PNIPAAm-co-AAc core) using MBAAm as a cross-linker.…”
Section: Strategies For Synthesis Of Pnipaam-based Hydrogelsmentioning
confidence: 99%
“…19 Herein, we aimed to fabricate monodisperse composite hollow particles of poly(N-isopropylacrylamide)/poly(ethyl-2-cyanoacrylate) (namely, poly(NIPAAm)/ poly(E2CA)) by using SPG emulsification, ionic, and photo-polymerization techniques. Poly(NIPAAm) is well known biocompatible polymer exhibiting volume phase transition temperature (VPTT) near lower critical solution temperature (LCST) around 35 o C. 3,20,21 Poly(E2CA), known as one of 'instant' adhesive family, is both biocompatible and biodegradable. In this work, we found that shell morphology of the composite hollow particles was changed from semi-interpenetrating network (semi-IPN) to double shell structure depending on the mass ratio of NIPAAm and E2CA monomers.…”
Section: Introductionmentioning
confidence: 99%